The future of learning : issues and prospects - Tokoro, Mario, 1947-; Steels, Luc (IOS Press ; Ohmsha, 2003)
Aims to publish multidisciplinary discussions that contribute to improving the education of children and adults of all ages, anywhere in the world. This book surveys results in cognitive neuroscience, artificial intelligence, and educational psychology, and also examines the potential uses of broadband and mass media in supporting education.